Dealing with slums in Egypt: Learning from the success factors of international experiences - Maher, Sylvia (AUC Knowledge Fountain, 2017)
The purpose of this study is to compile, analyze and present information on the current Egyptian government’s approaches for dealing with slums to enable the assessment of their success and sustainability. Those approaches are basically eviction, demolition and relocation (80% of the interventions), in situ development (20% of the interventions) and community participation. In addition, the thesis researches international experiences from the developing world, tackling in situ and relocation approaches. The cases were selected in order to come up with their success factors and shed light on their applicability to the Egyptian context. A case study using qualitative analysis demonstrates a typical example of the relocation approach adopted by the Egyptian government; that is Osman Housing (Masaken Osman) in Sixth of October City. In-depth interviews were conducted with the relocated residents from Deweka area to find out whether the government’s intervention solved their housing problem or not. The findings show that the Egyptian government’s relocation approach concentrated more on trying to eradicate existing slums rather than addressing the socio-economic drives that led to the growth of informal areas including urban poverty. This approach resulted in making the poor even poorer and slum dwellers even more marginalized. The thesis concludes with a set of recommendations based on the learned lessons and success factors of the international experiences introduced in the study, the literature review, and the realities and findings reflected in field work of the case study. These recommendations highlight the need for political and institutional support for intervention programs, promoting community participation and adopting a rights-based approach that recognizes that residents of slum areas have the same rights as other citizens in formal areas.